CALCULATING A BEAM OF VARIABLE SECTION LYING ON AN ELASTIC FOUNDATION - Akhmediev, Serik; Mikhailov, Valentin; Tazhenova, Gulzada; Bakirov, Madi; Filippova, Tatyana; Tokanov, Daniyar (Journal of Applied Engineering Science, 2022)
In this article, there has been studied the bending state of a reinforced concrete beam with a variable cross-sectional height along its length that rests along its entire length on a brick wall. The beam is under the action of arbitrarily located concentrated forces. The study has been performed on the basis of the original inhomogeneous differential equation of the 4th order, taking into account the external load and the bedding coefficients of the elastic foundation. Using the finite difference method, typical resolving finite difference equations have been obtained. A study of the influence of the degree of elasticity of the base, with a change in the value of the bed coefficients and elasticity parameters, was conducted. The results confirm the reliability of theoretical and practical calculations. Given theoretical provisions and applied results can be used in scientific research in the field of mechanics of a deformable solid body, as well as in practical design.